2018
DOI: 10.15405/epsbs.2018.04.02.52
|View full text |Cite
|
Sign up to set email alerts
|

Metaphorical Representation Of The Conflict In The German Mediadiskurce

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A quantitative analysis showed that none of the primary school textbooks contains, like the standard, the words "sustainable development", "sustainable development goals". (Ivanova, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A quantitative analysis showed that none of the primary school textbooks contains, like the standard, the words "sustainable development", "sustainable development goals". (Ivanova, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it seems natural, that regardless of the level of However, it cannot be said that the metaphor of ecological discourse is limited only to military ones. Morbial, mechanistic, religious and sports metaphors are also widely spread along with personification (Ivanova, 2015(Ivanova, , 2017Ivanova, Krivtsova, & Sannikova, 2018). Nechaeva (2016) writes about the concept "Order" in the German culture:…”
Section: Axiological Categoriesmentioning
confidence: 99%